Too fatigued to consume (ir)responsibly? The importance of work-related fatigue and personal values for responsible consumption - Grit Tanner; Marlies Schümann; Carolin Baur; Eva Bamberg (International Journal of Consumer Studies, 2021)
Research concerning the intention–behaviour gap in responsible consumption has assigned a crucial role to individuals' situational states and personal values in purchase situations. Concurrently, work psychology research has demonstrated that on-the-job experiences carry over to one's private life. Combining insights from responsible consumption research and action regulation theory from work psychology, we investigated whether a fatigued state after work mediates the relationship between perceived daily workload and responsible consumption behaviour in the evening. Moreover, we hypothesized that personal values interact with work-related fatigue in predicting responsible consumption behaviour. The data were collected through online surveys on four consecutive working days. The final sample consisted of 74 persons and 115 observations. To test our hypotheses, we used path analyses and controlled for the data structure. The results confirmed the predicted moderated mediation of environmentally responsible consumption; among the consumers who expressed high personal values in terms of the environment, a fatigued state was related to more responsible consumption. However, regarding socially responsible consumption focusing on fair production conditions, the results revealed a significant nonmoderated mediation. Our findings support the assumption that work experiences during the day affect responsible consumption behaviour in the evening, and thus, work should be given more consideration in consumer research. Further research is needed to specify the contextual factors leading to the positive relationship between fatigue and socially responsible consumption in terms of production conditions.
Keywords: 330; moderated mediation; personal values in terms of consumption; responsible consumption; work-consumption spillover; work-related fatigue